Kebijakan Penguatan Pesantren Dengan Program Mu’adalah - Umar, Muallief; Indarinul Mufidah, Luluk (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2024)
A form of strengthening in the current era of development and globalization, Mu'ida Islamic boarding schools are always struggling to maintain their identity by being open to external systems. By providing reinforcements to the education system, Islamic boarding schools have maintained their existence from time to time. This is usually characterized by shifts and changes according to the times and has high elastic power. If we look closely, there are two aspects that can be used to measure the success of a mu'ida Islamic boarding school's performance: first, government legality, namely when the Islamic boarding school is able to maintain its mu'idad status for the next four year period. Second, the standard quality of graduates, namely the products of Islamic boarding school graduates that comply with the internal quality standards set by the Islamic boarding school itself and the standards of market demands. There are three forms of strengthening mu'akan Islamic boarding schools, namely: curriculum renewal, method renewal and renewal in terms of optimizing Islamic boarding schools as centers for community development